The Impact of Video and Simulation Based Learning on Cognitive Development of Secondary School Students (Biology) - Dr. Quratulain; Natasha Sabir; Tehseen Anjum; Dr. Muhammad Usman Dar (Journal for Social Science Archives, 2025)
This research study explores how, technology integrated learning, using videos and simulations, influence the Cognitive development of secondary school science students in Biology Class. It distinct3 main area of Cognitive development, first, memory retention, second is critical thinking, while third one is problem- solving skills. The purpose of this study is to recognize whether using simulation and subject related videos in Science Classroom (Biology) enhances student understanding and learning outcomes as compared to traditional methodologies. A mixed method approach was used, combining both quantitative (pre-and posttests) and qualitative (students feedback) data to better understand the learning outcomes. A quasi-experimental research design was used involving both control and experimental group. Two groups were selected for this research. One group was taught traditional teaching methodologies and other group through video and simulation, pre and posttest Classroom observation, combining assessment, and student related surveys. The population was consisting of government secondary school students, through purposive sampling, a sample of 60 students were selected, 30 in the experimental group and 30 in the control group. A questionnaire was used to evaluate student’s perception and their cognitive outcomes. It was found through results that students who learned by technology_ integrated methodologies accomplished better in tasks specifically in (Cognitive) recalling information, solving Biology based difficulties and improved critical thoughts related to scientific concepts. This research finding supports provide significance perception for teachers, school leaders and curriculum developers to integrate and use technological enhanced tools to improved students learning outcomes.